Performance analysis of multi-energy sharing prosumers considering different load profiles - Zeng, Jincan; Wang, Peng; Wang, Qin; Liu, Minwei; Liu, Xi; Huang, Guori; He, Gengsheng; Yao, Shangheng; Li, Longxi (Frontiers in Energy Research, 2024)
With the advancement of distributed energy systems, energy sharing has emerged as a crucial trading mechanism on the demand-side, enabling participants to share self-generated energy with their neighbors through contractual agreements. Nevertheless, a comprehensive analysis is needed to balance the benefits among energy prosumers, given their distinct characteristics. This paper proposes a multi-energy sharing framework with flexible demand-side management based on full cooperation. We evaluate the economic and environmental performance of sharing participants, considering the impacts of different operation modes and diverse demand profiles. Cooperative game theory is employed to maximize the social welfare of all participants, with the different allocation schemes are used to distribute the cooperative surplus among stakeholders. The fairness of these schemes is assessed to ensure the feasibility and equity of the proposed framework. The results indicate that the centralized multi-energy sharing framework yields win-win outcomes for both individual and collective interests. Specifically, the total cost and carbon dioxide emissions of prosumers in the shared scenario are reduced by 13% and 16%, respectively, compared to individual operation scenarios. Moreover, thermal energy management is critically important for 1 Zeng et al.Performance of multi-energy sharing energy sharing. Furthermore, varying combinations of building types significantly affect cost savings and emission reductions, influencing energy sharing patterns and quantities.